Temperatures and qualities of light in Niger (Guizotia abyssinica (L.f.) Cass.) seeds germination in Mato Grosso do Sul, Brazil (2017)
For each vegetable species, there is a specific environment conditions to occur the seed germination process. However, there is a little information regarding the necessary conditions for Niger (Guizotia abyssinica (L.f.) Cass.) seeds germination. The aim of this research was to evaluate the influence of different temperatures and types of light on Niger (Guizotia abyssinica (L.f.) Cass.) seeds germination. Seeds were sown on two sheets of “germitest” paper inside plastic box type “gerbox” and placed on B.O.D. Treatments were constituted of two constant temperatures (15 ºC and 25 ºC, respectively) and an alternating temperature (20-30 ºC) under 10 hours for the lowest temperature and 14 hours for the highest temperature and they were associated to the wavelengths as follows: blue (440 nm), green (560 nm), red (660 nm), extreme red (730 nm), white light and dark. The experiment was conducted in a completely randomized design with four replicates of 50 seeds. Effects of different temperatures and qualities of light were evaluated by seeds germination and vigor. Higher germination of Niger seeds is observed in temperatures of 25 and 20-30 ºC and they can be considered as non-photoblastic.